2017
DOI: 10.1177/1012690217715642
|View full text |Cite
|
Sign up to set email alerts
|

‘I don’t think they realise how good we are’: Innovation, inclusion and exclusion in women’s Olympic boxing

Abstract: Marginalisation and exclusion of women in elite boxing has emerged as a substantial international problem, threatening women's democratic right to equal participation in sport. Since the London 2012 Olympic Games women's boxing has been an Olympic event. However, only 3 of the 10 weight categories were included in the Olympic programme for women. Today, male boxers compete in 10 out of 10 possible weight categories. While female boxers have gained accessed to a previously closed realm, discrimination, exclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 52 publications
1
18
0
7
Order By: Relevance
“…They were driven by economic necessity, although they all identified that they enjoyed their sports coach/instructors role and regarded it as ‘more than a job’. The results support Tjonndal’s (2017) that sport has cultural and structural changes, which give rise to greater entrepreneurial behaviour of individuals involved in new business creation. A number of respondents maximized their sporting knowledge by offering additional services to their sports customers such as sports massage and selling nutritional products.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…They were driven by economic necessity, although they all identified that they enjoyed their sports coach/instructors role and regarded it as ‘more than a job’. The results support Tjonndal’s (2017) that sport has cultural and structural changes, which give rise to greater entrepreneurial behaviour of individuals involved in new business creation. A number of respondents maximized their sporting knowledge by offering additional services to their sports customers such as sports massage and selling nutritional products.…”
Section: Discussionsupporting
confidence: 71%
“…These businesses can include a variety of different types depending on the context such as public/private partnerships or piggyback on existing sports clubs or organizations. The importance of environmental context for impacting sport entrepreneurship is evident in Tjonndal’s (2017) study of women’s boxing in which the author discussed how innovation is crucial in increasing the development of new sports. Moreover, Winard et al (2016) also utilized sports entrepreneurship theory by focusing on innovation to understand how the non-profit sport sector innovates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Desigualdades no que tange às questões de gênero são frequentes não apenas no karate, na capoeira e no MMA, mas também em diversas outras modalidades de luta, como pudemos encontrar na literatura (Appleby & Foster, 2013;Tjønndal, 2017;Woodward, 2014). No caso do boxe, percebe-se que a modalidade tem registro de pugilistas do gênero feminino já no século XVIII, mas trata-se de uma presença difícil e que tem sido marginalizada ainda hoje.…”
Section: Sobre Corpos Viris: O Imperativo Da Masculinidade Nas Amandecunclassified
“…Previous studies have explored the challenges women have faced in professional boxing ], female boxers' experiences of gender construction [Carlsson 2017], and their reduced opportunities and disadvantages [Cove and Young 2007] compared to their male counterparts. More recently, Tjønndal [2019a] explored the lived experiences of coaches and athletes in Norwegian Olympic boxing, as well as the innovation, inclusion and exclusion in women's Olympic boxing [Tjønndal 2019b]. Despite these valuable studies, from a sport psychology perspective, our understanding of the challenges female boxers face as well as strategies they have found effective in dealing with challenges across their sporting life span is limited.…”
Section: Phenomenological Interviewsmentioning
confidence: 99%